Analysis of the Effect Green Economy and Brown Economy on GDP in Indonesia, Thailand, Philippines in 2010-2020 - Ningtyas, Nadya Asoka; Andriyani, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study tries to compare the effect of the brown economy proxied by the CO2 Emissions, and Tourism Expenditures variable with the green economy proxied by the variables of Hydroelectricity, and Renewable Energy. The green economy is one of the solutions to environmental degradation. Methodology: This research is a form of comprehensiveness of previous research. This research is a type of quantitative research using the panel data regression analysis method. The data used in 2010–2020 was obtained from the World Bank and Our World in Data on three countries, Indonesia, Thailand, and the Philippines. Results: The results showed that EMS has a significant negative effect on GDP, while CEH and TE have a significant positive effect. Meanwhile, RE has a positive relationship but no significant effect. These results imply that the three countries have passed the second phase in the Kuznet curve of EKC theory. The great potential in green economy development has been utilized to maintain sustainable economic growth. Applications/Originality/Value The government is expected to support the optimization of the transition from non-renewable energy to renewable energy by utilizing all renewable energy components, including wind, biomass, and solar heat. Policymakers are expected to make policies that encourage tourism to adopt green tourism to overcome the adverse effects of tourist arrivals, and the government are expected to maximize and emphasize the application of hydroelectricity as a source of electricity.